Diseño y montaje de un prototipo para el control automatizado del sistema de riego por canales en el área de yamburara (vilcabamba) haciendo uso de hardware y software open source. - Ortega Kirby, Pablo Geovanny (2016)
The current irrigation system which has made the prototype of automation, it handled in a manual way this is a system which is controlled based on specific schedules for the use of water flow by users in certain time intervals, being the duct caretaker who provides this service. The duct has seven subsections which correspond to the inputs of flow to the orchards; each entry has a fixed period of time of use of the flow, for this reason it was made in automation a controlled periods of time system that the administrator irrigation should enter in the web GUI, where is possible to set the appropriate time, as well the administrator has the option of manual control through the interface that provides management of the gates in real time as directed by the administrator. In the development of this research project was described both physical and logic construction of a web automation system, which through algorithms gives to the system the option of an automatic control which functions based on sensors and effectors that are part of the PLC Arduino board. Through the interview with the responsible for the administration of the offices of the Board of Irrigation, users and duct caretaker was possible collect all the requirements for the design of the prototype system. Both the design, development as implementation of the prototype for the system, is based on methodological bases; methodologies as ICONIX forms part of development, because thanks to the description of diagrams that make this methodology is that it came to a better understanding of system operation, together with the XP methodology that underlies an increasingly rapid development in terms of systems.